Influence of implementation on mix promotion model strategy towards tourist visitation in Indonesia - Manafe, Janri D.; Setyorini, Tuti; Alang, Yermias A. Kay (International research journal of management, IT and social sciences, 2018)
This quantitative study aims at examining how the implementation of promotional mix model strategy, that consisted of nature tourism, arts, and culture, influencing the increase of both domestic and international tourists visitation in Indonesia. The study was conducted in Rote as a tourism Island that located in East Nusa Tenggara- Indonesia. Data itself obtained through questionnaires. Results shows that independent variables consisting of advertising, sales promotion and personal selling, have shown a significant influence and have given positive impact on tourist visitation to Rote Island. In other side, variables of public relations and direct marketing have no effect on tourist visitation to the Rote Island.